Strategi Aliansi Pemerintah Taiwan Terhadap Ancaman Republik Rakyat China dari Tahun 2018 - salsabila putri (Indonesian Journal of Peace and Security Studies (IJPSS), 2021)
This journal analyzes and describes what strategies are prepared by Taiwan to deal with threats from China. In this case, China has ambitions to regain control of Taiwan which they consider as part of its sovereignty. While Taiwan itself considers that they are an independent country. This study aims to see Taiwan's strategy in dealing with security threats from China. This research methodology uses descriptive qualitative research with a framework of thinking using the concept of Bandwagoning. By using this concept, it can be seen that Taiwan uses an alliance with the US to counter security threats from China. The strong form of the alliance between the two can be seen in the establishment of the Taiwan Relations Act (TRA) Security Agreement which is applied in the security agreement where the US is committed to protecting Taiwan from Chinese military attacks and selling weapons to Taiwan to ward off security threats from China